Influence of lanthanides on spin-relaxation and spin-structure in a family of Fe7Ln4 single molecule magnets12. Issue 11 (7th March 2018) - Prodius, Denis; Mereacre, Valeriu; Singh, Prashant; Lan, Yanhua; Mameri, Samir; Johnson, Duane D.; Wernsdorfer, Wolfgang; Anson, Christopher E.; Powell, Annie K.
Abstract : A family of undecanuclear Fe–Ln clusters, comprising butterfly motifs, was explored and two are found to behave as single molecule magnets. Abstract : A family of isostructural undecanuclear 3d–4f coordination clusters of formula [FeIII7LnIII4O4 (OH)3 (tea)2 (Htea)3 (Piv)7 (H2 O)2 (NO3 )3 ], where Ln = Y (1 ), Gd (2 ), Tb (3 ), Dy (4 ); PivH ≡ pivalic acid and H3 tea ≡ triethanolamine, was synthesised. The central Fe7 core of the coordination cluster can be described in terms of two Fe4 O2 butterfly motifs sharing a common body Fe atom. The two Fe4 mean-planes subtend a dihedral angle of ca. 72°. The Tb (3 ) and Dy (4 ) compounds show Single Molecule Magnet (SMM) behaviour as confirmed by ac-susceptibility and μ-SQUID measurements. Furthermore, 57 Fe Mössbauer spectra of1–4 confirm the presence of high-spin Fe III sites. The spectra of all complexes in the high temperature range (30–300 K) show broad overlapping doublets which were assigned to the body and wing-tip pairs of metal ions within the Fe7 core. The low temperature Mössbauer spectra show dependence on the nature of the rare-earth metal as a result of its interaction with the iron sites. Thus, we observed a transition from fast (2 ), to intermediate (1 ) and very slow (frozen) (3, 4 ) spin fluctuation phenomena in these compounds.